1995
DOI: 10.1288/00005537-199501000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Transoral laser resection with staged discontinuous neck dissection for oral cavity and oropharynx squamous cell carcinoma

Abstract: Transoral laser resection of oral cavity and oropharynx squamous cell carcinoma (OOSCC) is a widely accepted approach in the absence of cervical lymph node metastases. This study investigated the results of transoral laser surgery and discontinuous neck dissection (ND) for OOSCC with clinically obvious or suspected cervical node metastases. One hundred seventeen patients with infiltrating oral carcinoma were treated for cure with transoral resection of the primary and staged ND. Twenty-nine primaries were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 31 publications
3
24
1
2
Order By: Relevance
“…Compared to a previously reported all-inclusive, T1 to T4, TLM series by Eckel et al 10 ( n = 64), the current study had comparable DSS estimates for stages I to III, and slightly better outcomes for stage IV lesions (31% vs 21%, 10 respectively). Unlike our study, all neck dissections in the Eckel et al 10 series were staged.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Compared to a previously reported all-inclusive, T1 to T4, TLM series by Eckel et al 10 ( n = 64), the current study had comparable DSS estimates for stages I to III, and slightly better outcomes for stage IV lesions (31% vs 21%, 10 respectively). Unlike our study, all neck dissections in the Eckel et al 10 series were staged.…”
Section: Discussioncontrasting
confidence: 50%
“…Higher margin positivity has been documented in TLM studies on oral cancer in the absence of frozen sections. 10 Eckel et al, 10 reported a margin positivity rate of 37%, although residual tumor could be found in only 15% of the re-resections. This was attributed to nonavailability of frozen sections during the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several advantages to this approach weighed against the risks of protracting the time to start PORT as described above. We adopted the staged approach to the neck dissection to not only reduce the risk of fistula and surgical complications [28] but also to provide us with pathologic information at the primary site. This pathologic evaluation of the primary tumor can significantly influence the decision and recommendations for both neck dissection and/or adjuvant therapy to the ipsilateral and contralateral neck ( table 2 ).…”
Section: Current Treatment Approachmentioning
confidence: 99%
“…Moreover, successful treatment of stage II-IV lesions of the vocal folds, the supraglottic larynx, the oral cavity, and oro-and hypopharynx have recently been reported in the literature [14][15][16][17]. While the data presented in these studies indicate that TLS leads to oncological results that are comparable with more conventional treatment modalities in selected groups of patients, the potential role of laser surgery for larger series of unselected cases has not been settled to date.…”
Section: Introductionmentioning
confidence: 99%